Society online : the Internet in context - Howard, Philip N.; Jones, Steve (SAGE Publications, 2004)
Within the developed world, much of society experiences political, economic, and cultural life through a set of communication technologies barely older than many citizens. Society Online: The Internet in Context examines how new media technologies have not simply diffused across society, but how they have rapidly and deeply become embedded in our organizations and institutions. Society Online is not exclusively devoted to a particular technology, or specifically the Internet, but to a range of technologies and technological possibilities labeled "new media." Rather than trying to cover every p.